Water-extractable zinc protoporphyrin IX in Parma ham predominantly exists as complexes with hemoglobin and myoglobin. (April 2021) - Wang, Hung-Cheng; Hayakawa, Toru; Kumura, Haruto; Wakamatsu, Jun-ichi
Abstract: Zinc protoporphyrin IX (ZnPP) is the dominant red pigment in nitrate/nitrite free dry-cured hams such as Parma ham. A large amount of ZnPP in Parma ham is water-extractable and is thought to exist in complexes with unidentified water-soluble proteins. This study was done to clarify these ZnPP-binding proteins to provide insight into the ZnPP-forming mechanism. The ZnPP-binding proteins were purified from Parma ham water extract (PHE) through a combination of hydrophobic interaction chromatography, urea-PAGE, and SDS-PAGE, and finally identified as hemoglobin (Hb) and myoglobin (Mb). According to western blotting analysis of PHE, ZnPP-Hb and ZnPP-Mb complexes were observed as both intact and proteolyzed forms, and the formation of these complexes was independent of proteolysis. The amount of total ZnPP-Hb complexes was 3-fold higher than total ZnPP-Mb complexes. These results suggested that the heme destabilization in the heme pocket is important rather than proteolysis for forming ZnPP-binding proteins. Highlights: Zinc protoporphyrin IX (ZnPP)-binding proteins were separated using urea-PAGE. ZnPP-hemoglobin complex was predominant over ZnPP-myoglobin complex. Heme destabilization may be crucial for forming ZnPP-binding proteins. Formation of ZnPP-binding proteins was independent of proteolysis.